Statistical Analysis of Species Interaction and Optimization of Copper Flotation Process - Jena, Silpa Sweta; Pattanaik, Abhyarthana; Venugopal, R. (Journal of Mines, Metals and Fuels, 2022)
Studies have been carried out for analyzing the flotation performance of chalcopyrite ore from Rakha mines, Jharkhand. The full factorial methodology has been used for design of experiments. The reagents (collector and frother) dosages and time were independent variables and recovery and grade has been considered as responses. The minimum and maximum values of operating conditions were chosen after performing preliminary experiments at different operating conditions. The effect of the variables (species interaction - main and interactional) on recovery and grade were studied. In this work, the experimental data were compared to data obtained from the factorial design of experiments to check the validation of model. The results obtained for bulk were analyzed to calculate the optimized condition for effective recovery and grade.